2022
DOI: 10.1111/febs.16425
|View full text |Cite
|
Sign up to set email alerts
|

M1‐linked ubiquitination facilitates NF‐κB activation and survival during sterile inflammation

Abstract: Methionine 1 (M1)-linked ubiquitination plays a key role in the regulation of inflammatory nuclear factor-jB (NF-jB) signalling and is important for clearance of pathogen infection in Drosophila melanogaster. M1-linked ubiquitin (M1-Ub) chains are assembled by the linear ubiquitin E3 ligase (LUBEL) in flies. Here, we have studied the role of LUBEL in sterile inflammation induced by different types of cellular stresses. We have found that the LUBEL catalyses formation of M1-Ub chains in response to hypoxic, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In addition, it is well known that obesity induces the production of cytokines, such as TNF and IL-1b, which activate immune responses [13]. Hence, the findings described by Aalto et al [5] may have important implications for understanding the mechanisms behind obesity-associated inflammation. Could it be possible that M1-Ub is implicated in fine-tuning stress response and immune signalling during adipose tissue expansion?…”
Section: M1-ub In Hypoxia Associated With Obesitymentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, it is well known that obesity induces the production of cytokines, such as TNF and IL-1b, which activate immune responses [13]. Hence, the findings described by Aalto et al [5] may have important implications for understanding the mechanisms behind obesity-associated inflammation. Could it be possible that M1-Ub is implicated in fine-tuning stress response and immune signalling during adipose tissue expansion?…”
Section: M1-ub In Hypoxia Associated With Obesitymentioning
confidence: 90%
“…The authors observed increased M1-Ub levels in response to hypoxia and other stresses in CaCo2 cells and the inhibition of HOIP, using HOIPINs, prevented this [5]. However, no changes were observed during hypoxia or mechanical stress at the level of NF-jB activation in these cells.…”
Section: M1-ub In Cancermentioning
confidence: 94%
See 3 more Smart Citations